Diverse patterns of molecular changes in the mechano-responsiveness of focal adhesions - Malik Sheriff, Rahuman S. (2018)
Focal adhesions anchor contractile actin fibers with the extracellular matrix, sense the generated tension and respond to it by changing their morphology and composition. Here we ask how this mechanosensing is enabled at the protein-network level, given the modular assembly and multitasking of focal adhesions. To address this, we applied a sensitive 4-color live cell imaging approach, enabling monitoring patterns of molecular changes in single focal adhesions. Co-imaging zyxin, FAK, vinculin and paxillin revealed heterogeneities in their responses to Rho-associated kinase (ROCK)-mediated perturbations of actomyosin contractility. These responses were rather weakly correlated between the proteins, reflecting diverse compositional changes in different focal adhesions. This diversity is partially attributable to the location of focal adhesions, their area, molecular content and previous contractility perturbations, suggesting that integration of multiple local cues shapes differentially focal adhesion mechano-responsiveness. Importantly, the compositional changes upon ROCK perturbations exhibited distinct paths in different focal adhesions. Moreover, the protein exhibiting the strongest response to ROCK perturbations varied among different focal adhesions. The diversity in response patterns is plausibly enabled by the modular mode of focal adhesions assembly and can provide them the needed flexibility to perform multiple tasks by combining optimally a common set of multifunctional components.